Simulation and team training to improve preterm birth knowledge, evidence-based practices, and communication skills in midwives in Kenya and Uganda: Findings from a pre- and post-intervention analysis - Lara Miller; Phillip Wanduru; Josline Wangia; Kimberly Calkins; Hilary Spindler; Elizabeth Butrick; Nicole Santos; Leah Kirumbi; Dilys Walker (Public Library of Science (PLoS), 2023)
Simulation training in basic and emergency obstetric and neonatal care has previously shown success in reducing maternal and neonatal mortality in low-resource settings. Though preterm birth is the leading cause of neonatal deaths, application of this training methodology geared specifically towards reducing preterm birth mortality and morbidity has not yet been implemented and evaluated. The East Africa Preterm Birth Initiative (PTBi-EA) was a multi-country cluster randomized controlled (CRCT) trial that successfully improved outcomes of preterm neonates in Migori County, Kenya and the Busoga region of Uganda through an intrapartum package of interventions. PRONTO simulation and team training (STT) was one component of this package and was introduced to maternity unit providers in 13 facilities. This analysis was nested within the larger CRCT and specifically looked at the impact of the STT portion of the intervention package. The PRONTO STT curriculum was modified to emphasize prematurity-related intrapartum and immediate postnatal care practices, such as assessment of gestational age, identification of preterm labour, and administration of antenatal corticosteroids. Knowledge and communication techniques were assessed at the beginning and end of the intervention through a multiple-choice knowledge test. Clinical skills and communication techniques used in context were assessed through the use of evidence-based practiced (EBPs) as documented in video-recorded simulations through StudioCodeTM video analysis. Pre-and-post scores were compared in both categories using Chi-squared tests. Knowledge assessment scores improved from 51% to 73% with maternal-related questions improving from 61% to 74%, neonatal questions from 55% to 73%, and communication technique questions from 31% to 71%. The portion of indicated preterm birth EBPs performed in simulation increased from 55% to 80% with maternal-related EBPs improving from 48% to 73%, neonatal-related EBPs from 63% to 93%, and communication techniques from 52% to 69%. STT substantially increased preterm birth-specific knowledge and EBPs performed in simulation.